The Effect of the Team Games Tournament (TGT) Learning Model on the Indonesian Language Learning Outcomes of Fifth-Grade Students at SDN 106811 Bandar Setia - Qalbi, Nuri Alnasta; Lubis, Wildansyah; Halimatussakdiah, Halimatussakdiah; Rozi, Fahrur; Sembiring, Masta Marselina (The Future of Education Journal, 2025)
The problem in this study is that students are less active in learning because the learning carried out in class V SDN 106811 Bandar Setia has not used the right learning model, causing low student learning outcomes. The type of this research is Quasi Experimental with a research design of Nonequivalent Control Group Design. The subjects in this study were students with the research population used were all grade V students of SDN 106811 Bandar Setia totaling 40 students. The samples in this study were all VA class students totaling 20 students as the experimental class and VB class totaling 20 students as the control class. The data collection instruments in this study were test and observation instruments. The data analysis technique used in this research is quantitative analysis. The results showed that the average value in the experimental class treated with the Team Games Tournament (TGT) learning model was 81, the maximum score was 90 and the minimum score was 70. Then the average value in the control class using the expository model was 52,75 with a maximum score of 70 and a minimum score of 35. Based on the results of hypothesis testing using the t test, it is obtained that  > , namely the value of 10,13 > 2,02 so it can be concluded that Ha is accepted and Ho is rejected which means that there is an effect of the Team Games Tournament (TGT) learning model on the learning outcomes of Indonesian language students in the material of pantun class V SDN 106811 Bandar Setia.